FORMATION OF AN EFFECTIVE ENTERPRISE MANAGEMENT SYSTEM - CHEREP, ALLA; TOMAREVA-PATLAKHOVA, VIKTORIIA; KABANOVA, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article deals with methods of forming an effective enterprise management system based on the results of its diagnosis with the help of the most appropriate analytical tools. There are the method of calculation of integrated indicators of efficiency of resource potential management, commercial and financial activity of the enterprise and the general integrated indicator of efficiency of management system; methods of compiling a functional model of management evaluation; method of pairwise comparisons based on multidimensional scaling to take into account the negative impact of the most important external and internal factors. The application of these methods of diagnosing the effectiveness of the enterprise management system allows to outline the range of problems and shortcomings of the management subsystems, the most common of which are: reducing the profitability of goods, services, works; unsatisfactory liquidity of assets and concentration of equity; imperfection of motivation and coordination processes; inefficiency of communication processes, which is manifested in the inconsistency of managers' perceptions of the state of affairs in the organization to the assessments of employees.The system of measures to improve the efficiency of enterprise management is proposed, which consists of: measures to increase the profitability of goods (reduction of administrative, marketing and other operating costs, increase productivity by training and improving production skills, improving the nature and working conditions); measures to review and supplement the current system of employee motivation (formation of clear criteria for staff evaluation, analysis and consideration of real needs of employees, creating a differentiated reward system, providing (expanding) the social package, creating opportunities for career growth, involvement in decision making) ; measures to improve coordination actions during the performance of management functions; measures to establish effective internal communications; measures to improve the financial condition of the enterprise.
Keywords: efficiency; management system; diagnostic methods; integrated efficiency indicator; efficiency measures